GEOMETRIC AND LINEAR INDICES OF HEART RATE VARIABILITY DURING AN EXERCISE WITH FLEXIBLE POLE - Sarah M. Morini; Caio A. dos Santos; Ana M.S. António; Marco A. Cardoso; Luiz Carlos Abreu; Marcelo Tavella Navega; Rodrigo D. Raimundo; David M. Garner; Vitor E. Valenti (Российский кардиологический журнал, 2015)
Aim. Evaluate the acute effects of a standardized exercise with flexible pole on cardiac autonomic regulation.Material and methods. We evaluated 23 women between 18 and 25 years old and heart rate variability (HRV) was analyzed in the time (SDNN, RMSSD and pNN50), frequency domain (HF, LF and LF/HF ratio) and geometric analysis (RRTri, TINN, SD1, SD2 and SD1/SD2). The subjects remained at rest for 10 minutes. After the rest period, the volunteers performed the exercises with the flexible poles. Immediately after the exercise protocol, the volunteers remained seated at rest for 60 minutes and HRV were analyzed.Results. We observed no significant changes in the time domain and frequency domain indices of HRV between before and after single bout of exercise with flexible pole.Conclusion. A single bout of exercise with flexible pole did not induce significant change in geometric and linear indices of HRV.